Bimbingan Perkawinan: Persiapan Menuju Keluarga Sakinah (Studi pada KUA Singkawang Barat) - Adiansyah Adiansyah; Hanisah Hanisah; Maradona Maradona (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Efforts to realize the Sakinah family must be prepared from the beginning for the bride-to-be through marriage guidance. The research was carried out with a qualitative approach to data collection through interviews with Islamic Religious Extension Workers, Health Extension Workers from Health Centers and BKKBN and brides-to-be as guidance participants. The researcher also observed activities during the guidance and utilized the documentation of the activities. The results of the study show that marriage guidance was organized by KUA Singkawang Barat in collaboration with BKKBN and West Singkawang Health Center 1. The collaboration is in order to provide knowledge on physical and health, economic, social and psychological and socio-cultural resilience. The implementation of guidance is carried out every Monday and Thursday at KUA Singkawang Barat from 08.00 to 11.30 face-to-face. Islamic Religious Extension Counselor as a facilitator of material related to the foundation of the Sakinah family, aspects of psychology, marital dynamics, fiqh munakahat and conflict management in the household. Then from BKKBN focusing on preparing for the golden generation, family planning, child parenting, meeting needs and managing finances in the household. Furthermore, midwives and nurse facilitators from the West Singkawang 1 Health Center provided reinforcement about reproductive health. Differences in the educational and professional background of the bride-to-be are a challenge in providing guidance. Furthermore, it is necessary to add material related to law and legislation so that participants gain an understanding of the legal consequences in the event of divorce, domestic violence, or infidelity. In addition to marriage guidance, KUA Singkawang Barat has a new breakthrough that will be carried out in the form of guidance to the scavenger community, former commercial sex workers, Nafza Residents and the elderly who are in the Nitizen Cinta Singkawang (NCS).